Women’s Empowerment and Social Forestry Management Dynamics: Analysis of Community Forest Scheme in Sungai Gelam Village - Dani Sirait; Michael Lega; Fajar Alan Syahrier (JURNAL ILMIAH DETUBUYA, 2026)
This study analyzes the dynamics of social forestry management through the Community Forest scheme in Sungai Gelam, Muaro Jambi Regency, with a specific focus on women's empowerment within prolonged tenurial conflicts. The research employs a descriptive qualitative approach, using in-depth interviews, field observations, and document analysis to collect data. The findings indicate that internal conflicts within the Bersatu Arah Maju (BAM) Cooperative and land disputes with the Karya Makmur Farmer Group significantly hinder women's participation in forest management. Although the Community Forest scheme is designed to empower marginal communities, including female-headed households, its implementation faces structural barriers such as tenurial conflicts, institutional legal uncertainty, and patriarchal dominance in decision-making. The 2024 suspension of the BAM Cooperative's Community Forest Business Utilization License (Izin Usaha Pemanfaatan Hutan Kemasyarakatan/IUP-HKm), covering 501 hectares, demonstrates a governance failure that fails to prioritize gender inclusivity. This study recommends strengthening gender-responsive institutions, community-based conflict mediation, and affirmative policies to enhance women's access to and control over forest resources.